The sunny-luna travelling oracle ebook - Pleece, Warren (Dark Horse Comics, LLC., 2024)
Esta, a lonely, book-hungry, restless teen, must fight to save the planet in this eco-noir graphic novel thriller that’s part Fahrenheit 451 and part Station Eleven.In the devastated dystopian dust bowl of what was once America, a mesmerizing stage show called The Sunny-Luna Travelling Oracle comes to Esta's town. When Sunny and Luna take an interest in her, it feels like her ticket out.But these mysterious proprietors are secretly members of a harsh authoritarian order, and they have a hidden agenda: scavenge for mythic texts that hold the last hope for reviving a natural world—and destroy them. Esta is the unwitting key to this strange magic, and she soon finds herself literally transported to a supernatural Wonderland—and the twisted plot of Sunny and Luna.From the acclaimed storyteller Warren Pleece (Incognegro, Hellraiser, Deadenders), perfect for fans of dystopian crime and mystery comics such as Sweet Tooth and Paper Girls.